Outsourcing issues in the pharmaceutical industry - Lee, Sze Hwee (2008)
Due to the prominence of the pharmaceutical industry, this paper explored the outsourcing issues in this industry. Understanding of the activities outsourced and the main motives were obtained together with the vendor selection process and the monitoring mechanisms involved. Future trends and the overall outlook of outsourcing were also covered.